Effect of Video-Feedback System utilizing SMART system on junior competitive swimmer`s motivation and swimming performance - Sengoku, Y.; Shimojo, H.; Sugimoto, S.; Miyaji, C.; Nomura, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The purpose of the present study was to identify the effect of Video-Feedback System (V-FBS) utilizing SMART system on junior competitive swimmer`s motivation and swimming performance. Eleven junior competitive swimmers attending in a private swimming club participated in this study (Experimental group: EX n=4, Control group: CON n=7, age: 12.0±1.6). Swimmer`s under water swimming motion through the training session were filmed once a week and presented to the EX utilizing SMART system one week after. CON merely took part in the ordinary training session. It was indicated that the measurement data were equivalent to 2.49 stroke reduction in EX for swimming 25 m compared to 1.48 stroke reduction in CON. Furthermore EX will exceed 1.5 m for ten strokes in SL improvement (EX: 4 m, CON: 2.5 m). Consequently it was concluded that V-FBS has an effect to improve swimming technique for junior competitive swimmer more effectively.